Os adolescentes e o uso do whatsapp: la??os e embara??os nas suas sociabilidades - Munh??z, ??ngelo Caminha (2016)
With the objective of analysing how teenagers appropriate the message app for mobile devices WhatsApp and what are the consequences of this process to their sociabilities, an exploratory study was made with thirteen students, of ages of 15 to 18 years, of both sexes, in a public high school of the Distrito Federal. The theoretical foundation was based on Simmel, L??vy and Castells, among others. The data was collected by means of questioners and implementation of two focal groups and the material was given a qualitative treatment by means of the Bardin's Content Analysis Technique. As the main results, the fluent appropriation of the WhatsApp app in their daily routine, mostly in a modest to intense way, stands out. However, the app is still not primarily used in their interactions with their social groups, prevailing, still, the face-to-face interactions. The online and offline communication are interchanged. They are motivated to use it by the need of immediate and ubiquitous communication, which the app makes available in an easy and simple way, allowing continuous connectivity, intrinsic to contemporary times. Also, as motivation, they receive influence from friends and colleagues, from the capitalist market and from the families' financial condition. As opportunities for their sociabilities, they pointed out the maintenance and intensification of their relationships, sociality and enlargement of their contact network. In relation to the challenges, they indicated the communication conflicts, digital privacy and the sporadic showing of psychic and physical symptoms. The consequences regarding their sociabilities transpired in dualistic manner as bonds and awkwardness, chiefly in their basic social circles. In the friend circle, the bonds arise from the intensity and warmth with which they interact. The awkwardness, among others, from the fear of exclusion from the group, conflicts and the matter of privacy. In the family circle, seeking security, they contact their parents through WhatsApp, keeping the primary bonds. The restriction to the use of the app, the absence of familiar talking groups or in an unpleasant participation generate the awkwardness. On the social school circle, given opportunity by the resources made available by the app, they become collaborative in sharing the school tasks, registering the subjects needed to be studied and participating in groups of student interest. The awkwardness arise from the restraint of the use inside classroom and from the pretentious neutrality of the school regarding the prevention of cyberbullying. The conclusions are preliminary, induced by the literature review and the interpretation reported by the researched. In face of this, we understand that the communication technology advances that are happening in the 21st century requires of the academic knowledge new researches seeking to analyse the possible consequences in the experience of the teenagers.